Esther Hines: Culturally Competent Collaboration to Manage Diabetes - Gail Marion; Carol Hildebrandt; Sonia Crandall; Julienne Kirk (Association of American Medical Colleges, 2011)
Abstract This resource is an 11-minute video with Facilitator Guide designed to be used formatively to instruct providers and health professions learners how to apply culturally responsive, patient-centered communication skills to effectively counsel patients on blood sugar control and weight loss. The video is not intended to portray a perfect provider-patient interview but rather an effective encounter to begin to address short- and long-term lifestyle strategies for improved patient health. Learners are encouraged to use the "6As" (Agenda Set, Assess, Advise, Agree, Assist, Arrange) and to consider the patient's health literacy level in exploring her perspective and negotiating a plan that will help her to more effectively address necessary lifestyle changes. The video was evaluated by three standardized patient instructors with experience as both a standardized patient for a diabetes counseling case and an instructor providing feedback using the Diabetes Risk Factor Interview Scale (DRFIS). Interrater reliability on the 12 DRFIS domains averaged 4.5. The resource can be used with a wide variety of health professions learners. It has been used for orientation to basic communication and counseling skills for first-year physician assistant students, in preparation for a diabetes counseling standardized patient encounter, and to introduce third-year medical students in the family medicine clerkship to effective counseling skills.